Test of Anderson-Stuart model in sodium silicate glasses and the general Arrhenian conductivity rule in wide composition range - Nascimento,M. L. F. (2006)
We collected and analyzed literature data on ionic conductivity sigma and activation energy E A in the binary sodium silicate system in a wide composition range. The Anderson and Stuart model has been considered to describe the decreasing tendency of activation energy E A with alkali concentration in this system. In this analysis were considered experimental parameters, such as shear modulus G and relative dielectric permittivity epsilon. A general conductivity rule is found in 194 of 205 glasses, when one plots log sigma vs. E A/kB T, where kB is the Boltzmann constant and T is the absolute temperature. This fact means that the arrhenian relation has universal uniqueness of form sigma = sigma (E A,T) in wide Na2O composition range. The results also show that there is strong correlation by more than 19 orders of magnitude on conductivity with E A/kBT. An explanation for this behavior links ionic conductivity and microscopic structure. The problem of phase separation in this system is also considered.